2014
DOI: 10.1002/mnfr.201400286
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate and nitrite in the diet: How to assess their benefit and risk for human health

Abstract: Nitrate is a natural constituent of the human diet and an approved food additive. It can be partially converted to nitrogen monoxide, which induces vasodilation and thereby decreases blood pressure. This effect is associated with a reduced risk regarding cardiovascular disease, myocardial infarction, and stroke. Moreover, dietary nitrate has been associated with beneficial effects in patients with gastric ulcer, renal failure, or metabolic syndrome. Recent studies indicate that such beneficial health effects d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
108
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(113 citation statements)
references
References 231 publications
(278 reference statements)
2
108
0
3
Order By: Relevance
“…Beetroots from Rio Grande do Norte showed significantly high NO 2 − content when compared to beetroots from Minas Gerais, Bahia, Rio (Habermeyer et al 2015). Agricultural (type of cultivation, fertilization, use of herbicides, and availability of other nutrients) and environmental (atmospheric humidity, temperature, exposure to sunlight, and light intensity) factors are the factors that most affect NO 3 − content in beetroots (Santamaría 2006;Habermeyer et al 2015). Originally from European and North African regions, the beetroot is a vegetable typical of temperate climates, which adapts well in temperatures between 10 and 20°C (Tullio et al 2013).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Beetroots from Rio Grande do Norte showed significantly high NO 2 − content when compared to beetroots from Minas Gerais, Bahia, Rio (Habermeyer et al 2015). Agricultural (type of cultivation, fertilization, use of herbicides, and availability of other nutrients) and environmental (atmospheric humidity, temperature, exposure to sunlight, and light intensity) factors are the factors that most affect NO 3 − content in beetroots (Santamaría 2006;Habermeyer et al 2015). Originally from European and North African regions, the beetroot is a vegetable typical of temperate climates, which adapts well in temperatures between 10 and 20°C (Tullio et al 2013).…”
Section: Discussionmentioning
confidence: 89%
“…The main finding of the present study was that beetroots from Rio de Janeiro showed significantly high NO 3 − content when compared to beetroots from Rio Grande do Norte, Santa Catarina, Minas Gerais, and Bahia. Beetroots from Rio Grande do Norte showed significantly high NO 2 − content when compared to beetroots from Minas Gerais, Bahia, Rio (Habermeyer et al 2015). Agricultural (type of cultivation, fertilization, use of herbicides, and availability of other nutrients) and environmental (atmospheric humidity, temperature, exposure to sunlight, and light intensity) factors are the factors that most affect NO 3 − content in beetroots (Santamaría 2006;Habermeyer et al 2015).…”
Section: Discussionmentioning
confidence: 96%
“…Likewise, presence of nitrates and nitrites in agricultural products have significant influence on human health and is an important indicator of fertilizer quality. Very recent literature [15] affirms that beneficial health effects (such as reduced risk of cardiovascular disease) are attainable by daily consumption of nitrate-rich vegetables. However, enhanced risk of cancer from ingested nitrate and nitrite cannot be ruled out.…”
Section: Introductionmentioning
confidence: 98%
“…However, nitrate can decrease blood pressure, thus reducing the risk of cardiovascular disease, myocardial infarction, and stroke. Daily consumption of nitrate-rich vegetables is associated with beneficial effects for patients with gastric ulcer, renal failure, and metabolic syndrome (Habermeyer et al, 2015).…”
Section: Introductionmentioning
confidence: 99%